Social-Economic Polemic on the Local Government Land and Building Tax Administration System in Indonesia - Samudra, Azhari Aziz; Mayasari, Diana (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2024)
This research aims to determine the substance of the differences in the Land and Building Taxes (LBT) tax administration system during the Dutch colonial period, after independence, and after-tax reform until now. This study questions why local governments have only been able to be autonomous now, even though the potential for LBT is very high. This research uses a qualitative methodology with a comparative descriptive approach that compares two or more conditions and events through literature related to the socio-economic polemic paradigm. The research results reveal, first, the long history of the Dutch being in power, which shows that they introduced Landrente (LBT) on the island of Java, and then the British changed it to a land rental system. When the Dutch returned to power, they reapplied Landrente by force. Second: Administratively and legally, history shows that this tax belongs to the region and must be used for regional development. However, the central government is only willing to hand over a few tax objects because the potential for LBT is broad and has political elements. The conclusion shows that historical evidence validly proves that LBT is a tax intended for local governments to achieve regional autonomy. The local government needs to convince the central government to accelerate regional autonomy; the central government should hand over the management of all LBT objects to the local government with guidance from the central government.